Pathogenicity and characteristics of Blastocystis subtypes - Nurul Ain; Afifa Radhina; Mike Permata Sari (Indonesian Journal of Health Science, 2026)
Blastocystis sp., an intestinal protozoan widely distributed in the human gastrointestinal tract, exhibits a global presence, with prevalence varying by region and generally higher in developing countries compared to developed ones. In Indonesia, reported prevalence varies considerably by region and study population, ranging from approximately 34% to 72% in several regional studies. This protozoan is water-borne and primarily transmitted through cysts via the fecal-oral route. Factors such as poor hygiene, immigration, travel to tropical developing countries, contact with animals, and consumption of contaminated food or water elevate the risk of infection. The pathogenesis in humans remains unclear, as infections may either manifest symptoms or remain asymptomatic, partly due to diagnostic limitations and variation in virulence across subtypes. This review aims to elucidate the characteristics and pathogenicity of Blastocystis sp. subtypes, particularly ST3, which is frequently dominant in symptomatic patients, and to discuss ongoing controversies in the literature.